Epigenetic regulation of transcription factor promoter regions by low-dose genistein through mitogen-activated protein kinase and mitogen-and-stress activated kinase 1 nongenomic signaling. Issue 1 (December 2016) - Yu, Linda; Ham, Kyle; Gao, Xiaohua; Castro, Lysandra; Yan, Yitang; Kissling, Grace; Tucker, Charles; Flagler, Norris; Dong, Ray; Archer, Trevor; Dixon, Darlene
Abstract Background The phytoestrogen, genistein at low doses nongenomically activates mitogen-activated protein kinase p44/42 (MAPKp44/42 ) via estrogen receptor alpha (ERα) leading to proliferation of human uterine leiomyoma cells. In this study, we evaluated if MAPKp44/42 could activate downstream effectors such as mitogen- and stress-activated protein kinase 1 (MSK1), which could then epigenetically modify histone H3 by phosphorylation following a low dose (1 μg/ml) of genistein. Results Using hormone-responsive immortalized human uterine leiomyoma (ht-UtLM) cells, we found that genistein activated MAPKp44/42 and MSK1, and also increased phosphorylation of histone H3 at serine10 (H3S10ph) in ht-UtLM cells. Colocalization of phosphorylated MSK1 and H3S10ph was evident by confocal microscopy in ht-UtLM cells (r = 0.8533). Phosphorylation of both MSK1and H3S10ph was abrogated by PD98059 (PD), a MEK1 kinase inhibitor, thereby supporting genistein's activation of MSK1 and Histone H3 was downstream of MAPKp44/42 . In proliferative (estrogenic) phase human uterine fibroid tissues, phosphorylated MSK1 and H3S10ph showed increased immunoexpression compared to normal myometrial tissues, similar to results observed in in vitro studies following low-dose genistein administration. Real-time RT-PCR arrays showed induction of growth-related transcription factor genes, EGR1, Elk1, ID1, and MYB (cMyb) with confirmation by western blot, downstream of MAPK in response to low-dose genistein in ht-UtLM cells. Additionally, genistein induced associations of promoter regions of the above transcription factors with H3S10ph as evidenced by Chromatin Immunoprecipitation (ChIP) assays, which were inhibited by PD. Therefore, genistein epigenetically modified histone H3 by phosphorylation of serine 10, which was regulated by MSK1 and MAPK activation. Conclusion Histone H3 phosphorylation possibly represents a mechanism whereby increased transcriptional activation occurs following low-dose genistein exposure.